Meningkatkan Aktivitas dan Hasil Belajar Mata kuliah Teori Probabilitas Semester 2 Prodi Pendidikan Matematika FKIP UNBARI Jambi Melalui Metode Permainan Kartu - Relawati Relawati; Eni Defitriani (Jurnal Ilmiah Universitas Batanghari Jambi, 2018)
Probability theory is one of the subjects that are difficult to understand by students semester 2 Prodi mathematics education. This can be seen from the low activity resulting in low yield learning probability theory students. This research aims to find out whether the method learning card games can increase the activity of students and student learning outcomes. Research conducted on students semester 2 Prodi mathematics education FKIP UNBARI lesson 2017/2018 year is a research action research which is a combined approach of quantitative and qualitative approaches. Research done in cycles. Each cycle consists of four steps, namely planning, implementation, observation and reflection. The data was collected by using the observation sheet for student activity data and test results for learning. Research findings show that learning mathematics with the method of card games can increase the activity and results of student learning math semester 2 Prodi mathematics education. Based on the results of the study it can be concluded that learning with the method of card games can increase the activity of the students and the results of learning probability theory students semester 2 Prodi mathematics education FKIP UNBARI.